The method of english text's computerized formation in accordance with the propagandist's psycholinguistic portrait - Тарасенко, Ярослав Володимирович (Ukrainian Information Security Research Journal, 2020)
The current situation in the country and in the world requires the development of reliable methods for detecting and neutralizing cyber threats, one of which is information propaganda in media sources. To counter such a threat, it is necessary to carry out the reverse influence on the propagandist, which can be realized on the basis of a computer-generated meaningful text based on the propagandist's psycholinguistic portrait. The vast majority of modern methods for computerized text generation are based on machine learning technologies, which limits the ability of effectively building a psycholinguistic profile due to the need for a large amount of input information, and this leads to the risk of detecting the propaganda counteraction. Other methods do not take into account the categorical and quantum nature of perception, they are too demanding on the input information amount to build the contextual connections, or do not take into account the propaganda discourse. It was developed the method of English text's computerized formation in accordance with the propagandist's psycholinguistic portrait based on multilevel templates and improved methods of natural language data forest, by using the methods of quantum semantics and Montague semantics, which allows to increase the effectiveness of counteracting the negative impact of English-language propaganda, due to the taking into account propagandist's individual subjective semantic line and the probable quantum states of lexical-semantic units, based on the semantic particle's classification. The method allows generating the English-language text in accordance with the propagandist's psycholinguistic portrait for further implementing in it the means of reverse target influence on the propagandist. The method's use is important in studying the problem of shifting the text's semantic line in the direction of the propagandist's subjective semantic line.